2010
DOI: 10.1002/bit.22606
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of bacterial surface electrostatic potential and pH upon adhesion to a solid surface and impacts to cellular bioenergetics

Abstract: In our previous study [Hong Y, Brown DG (2009) Appl Environ Microbiol 75(8):2346-2353], the adenosine triphosphate (ATP) level of adhered bacteria was observed to be 2-5 times higher than that of planktonic bacteria. Consequently, the proton motive force (Delta p) of adhered bacteria was approximately 15% greater than that of planktonic bacteria. It was hypothesized that the cell surface pH changes upon adhesion due to the charge-regulated nature of the bacterial cell surface and that this change in surface pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…E. coli, B. subtilis and P. putida responded similarly to changes in pH and this is seen by the grouping of their confidence intervals, whereas S. epidermis shows distinct deviation from this grouping. When considered in context with our prior work on the variation in bacterial ATP upon adhesion [1][2][3][4][5], these results suggest that S. epidermis adhesion to acidic surfaces would have no effect on cellular bioenergetics, while its adhesion to basic surfaces will have an enhanced effect compared to other neutrophilic bacteria. This information may be useful in identifying and developing antibacterial materials, coatings and solutions to discourage S. epidermidis colonization of surfaces.…”
Section: Relationship Between Atp and Extracellular Phmentioning
confidence: 63%
See 4 more Smart Citations
“…E. coli, B. subtilis and P. putida responded similarly to changes in pH and this is seen by the grouping of their confidence intervals, whereas S. epidermis shows distinct deviation from this grouping. When considered in context with our prior work on the variation in bacterial ATP upon adhesion [1][2][3][4][5], these results suggest that S. epidermis adhesion to acidic surfaces would have no effect on cellular bioenergetics, while its adhesion to basic surfaces will have an enhanced effect compared to other neutrophilic bacteria. This information may be useful in identifying and developing antibacterial materials, coatings and solutions to discourage S. epidermidis colonization of surfaces.…”
Section: Relationship Between Atp and Extracellular Phmentioning
confidence: 63%
“…In recent work, we demonstrated that bacterial attachment to a surface can impact cellular bioenergetics, with the effect related to the types and surface densities of acid/base functional groups on the bacterial and solid surfaces [1][2][3][4][5]. Specifically, we have demonstrated that surfaces with acidic functional groups can enhance bacterial activity, measured as an increase in cellular adenosine triphosphate (ATP), whereas surfaces with basic functional groups can decrease cellular ATP.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations